Ponrepo Viktor 1860-1926 (1931) - Marek, Lubos (Iluminace, 2018)
Lubos Marek's text charts the life and business activities of Dismas Slambor, known as Viktor Ponrepo, a pioneer of Czech cinema, from his beginnings as a magician and operator of a traveling cinema to the founding of the first permanent cinema in Prague, while also drawing attention to specific archival materials stored in the National Film Archive.
Keywords: Viktor Ponrepo; Dismas Slambor; traveling cinema; permanent cinema; National Film Archive